Green Marketing Strategy in the Age of Sustainability: Building an Environmentally Friendly Brand Image for Long-Term Competitive Advantage - Sultan, Taqwa; Dioh, Septia S. (PT. Anagata Sembagi Education, 2025)
This study examines the impact of green marketing strategy on green brand image and sustainable competitive advantage among Indonesian companies adopting environmentally friendly business practices. Using a quantitative-explanatory design, data were collected from 150 marketing and CSR managers through purposive sampling. The findings reveal that green marketing strategies particularly eco-innovation, energy efficiency, and environmentally focused communication positively and significantly affect both green brand image and sustainable competitive advantage. Moreover, green brand image mediates the relationship between green marketing strategy and competitive advantage, indicating that authentic and consistent sustainability efforts enhance consumer trust, brand equity, and long-term competitiveness. These results underscore the strategic importance of integrating green values across the value chain to achieve both environmental responsibility and market differentiation. The study contributes theoretically by strengthening the empirical link between sustainable marketing and brand-based competitive advantage, and practically by providing actionable insights for corporations seeking to align profitability with sustainability in the era of the green economy.